Dying to work: Effects of unemployment insurance on health - Alexander Ahammer; Analisa Packham (Johannes Kepler University of Linz, Department of Economics, 2020)
Using administrative data for Upper Austrian workers from 2003-2013, we show that an extension in unemployment insurance (UI) duration increases unemployment length and impacts worker physical and mental health. These effects vary by gender. Specifically, we find that women eligible for an additional 9 weeks of UI benefits fill fewer opioid and antidepressant prescriptions and experience a lower likelihood of filing a disability claim, as compared to non-eligible unemployed women. Moreover, estimates indicate within-household spillovers for young children. For men, we find that extending UI benefit duration increases the likelihood of a cardiac event and eventual disability retirement filing.
Keywords: I38; I18; J18; 330; Unemployment insurance; health; disability; opioids